2023
DOI: 10.1039/d2lc01158a
|View full text |Cite
|
Sign up to set email alerts
|

A hiPSC-derived lineage-specific vascular smooth muscle cell-on-a-chip identifies aortic heterogeneity across segments

Abstract: Aortic aneurysm (AA), a potentially lethal condition with the characteristic of aortic dilatation, can only be treated by surgical or endovascular procedures. Underlying mechanisms of AA are unclear and early...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The underlying mechanism of AA is still unclear due to the heterogeneity of the segmental aorta and the limitations of existing disease models, resulting in insufficient investigation into early preventive treatment. Liu et al [ 70 ] established a comprehensive lineage-specific VSMCs-on-a-chip model using hiPSCs to generate cell lineages representing different segments of the aorta. They integrated this organ chip model with high-tech tools, such as transcriptomics, and conducted many experiments, including RNA sequencing, real-time reverse transcriptase-polymerase chain reaction, immunofluorescence, western blotting, and FACS analyses, to study the heterogeneity of the response of the segmental aorta to tensile stress and drug testing.…”
Section: Disease Modelingmentioning
confidence: 99%
“…The underlying mechanism of AA is still unclear due to the heterogeneity of the segmental aorta and the limitations of existing disease models, resulting in insufficient investigation into early preventive treatment. Liu et al [ 70 ] established a comprehensive lineage-specific VSMCs-on-a-chip model using hiPSCs to generate cell lineages representing different segments of the aorta. They integrated this organ chip model with high-tech tools, such as transcriptomics, and conducted many experiments, including RNA sequencing, real-time reverse transcriptase-polymerase chain reaction, immunofluorescence, western blotting, and FACS analyses, to study the heterogeneity of the response of the segmental aorta to tensile stress and drug testing.…”
Section: Disease Modelingmentioning
confidence: 99%
“…An “aorta on a chip” approach in congenital aortic valve disease demonstrated impaired mitochondrial function due to suppression of NOTCH1 , reducing VSMC contractility which was partially rescued with drug treatment ( 172 ). Liu et al ( 173 ) developed a VoC model with VSMCs of all three aortic lineages in series and determined the differential response to Ciprofloxacin and identified the PI3K-Akt signalling pathway as key in response to stretch ( 173 ). It should be noted that these “aorta on a chip” models do not reflect the structure, scale and stress in the aortic wall and so their predictive power over simpler systems is debatable.…”
Section: Complex Three-dimensional Disease Modelsmentioning
confidence: 99%
“…91,92 Some of the most common and recently developed 3D cell culture techniques for hiPSC-derived SMCs involve the usage of organ-on-a-chip, vascular cell spheroids, and engineered vascular tissues (eVTs) to name a few. [93][94][95] The ongoing diversification of these techniques has exponentially increased within the last decade, attracting more attention to the potential that 3D models have for the study of vascular function and disease. Threedimensional cultures allow for the proper formation of and interaction with the ECM, mimicking cell adhesion behaviors as well as migratory and differentiation cues that are present in vivo.…”
Section: Three-dimensional Culture Systemsmentioning
confidence: 99%
“…Disease modeling using eVTs has enabled researchers to fine-tune the attributes of hiPSC-SMCs to reflect in vivo conditions more accurately. To develop an alternative for aortic aneurysm mouse models, Liu et al 93 established a linage-specific SMC-on-a-chip model using hiPSC-SMCs derived via different cell lineages that would represent different segments of the aorta. These lineages were then tested through various tensile stress conditions, which revealed that all lineages of hiPSC-SMCs within the organ-on-a-chip model upregulated pathways related to cellular contraction and adhesion in response to optimized cyclic stretch as expected, but the test also revealed lineage-based differences in sensitivity to tensile stress.…”
Section: Applications Of Hipsc-smcsmentioning
confidence: 99%
See 1 more Smart Citation